2009
DOI: 10.1186/1471-2407-9-23
|View full text |Cite
|
Sign up to set email alerts
|

Total laparoscopic hysterectomy versus abdominal hysterectomy in the treatment of patients with early stage endometrial cancer: A randomized multi center study

Abstract: BackgroundTraditionally standard treatment for patients with early stage endometrial cancer (EC) is total abdominal hysterectomy and bilateral salpingo oophorectomy (TAH+BSO) with or without lymph node dissection through a vertical midline incision. While TAH is an accepted effective treatment, it is highly invasive, visibly scarring and associated with morbidity. An alternative treatment is the same operation by laparoscopy. Though in several studies total laparoscopic hysterectomy (TLH+ BSO) seems a safe and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 16 publications
1
41
0
2
Order By: Relevance
“…Six studies were further excluded including one study for no available data (Nicklin et al, 2011) and 5 overlapping studies (Tozzi et al, 2005;Zullo et al, 2005;Bijen et al, 2009;. Finally, nine randomized controlled trials with a total of 1263 patients were included into this meta-analysis (Fram, 2002;Tozzi et al, 2005;Zorlu et al, 2005;Chen and Huang, 2007;Wang, 2008;Malzoni et al, 2009;Zullo et al, 2009;Janda et al, 2010;Mourits et al, 2010).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Six studies were further excluded including one study for no available data (Nicklin et al, 2011) and 5 overlapping studies (Tozzi et al, 2005;Zullo et al, 2005;Bijen et al, 2009;. Finally, nine randomized controlled trials with a total of 1263 patients were included into this meta-analysis (Fram, 2002;Tozzi et al, 2005;Zorlu et al, 2005;Chen and Huang, 2007;Wang, 2008;Malzoni et al, 2009;Zullo et al, 2009;Janda et al, 2010;Mourits et al, 2010).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The disadvantages of monitoring a learning curve in this manner is that it is time consuming and costly. In the present study, the visiting surgeon was supported by UMCG in an educational setting, and the study was a preparation for a larger trial [16]. We would suggest that with this study we demonstrated that a guided learning curve by an experienced colleague, using OSATS as the feedback instrument and for assessment, is a safe way to implement an advanced laparoscopic technique.…”
Section: Discussionmentioning
confidence: 69%
“…Because the advantages of laparoscopy over laparotomy in terms of quality of life and costeffectiveness can be proved only in a randomized study, we currently are conducting a multicenter, prospective, randomized controlled trial in the Netherlands [16]. All gynecologists who participated in the present study are participating in this randomized controlled trial, which reflects effective implementation of LH in these hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, whilst endometrial cancer is the first gynecologic cancer to be treated laparoscopically, a laparoscopic approach also is being used for the surgical management of malignant disease. Following the first report on the use of laparoscopic surgery for endometrial cancer by Childers et al [12], the feasibility, safety, and efficacy of laparoscopic surgery in the surgical management of endometrial cancer has been reported in numerous retrospective studies [13][14][15][16][17][18][19][20][21][22][23][24][25], prospective nonrandomized studies [26][27][28][29], or randomized, controlled trials (RCTs) [30][31][32][33][34][35][36][37][38][39][40][41][42]43 This review provides an update on the role of laparoscopic surgery for the surgical management of endometrial cancer with particular emphasis on feasibility, safety, and efficacy based on the results of randomized, controlled trials comparing laparoscopy and laparotomy for surgical staging of endometrial cancer.…”
Section: Introductionmentioning
confidence: 99%